2021
DOI: 10.1088/1361-6528/ac0e69
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of boron-based hybrid monolayers

Abstract: Anisotropic 2D Dirac cone materials are important for the fabrication of nanodevices having direction-dependent characteristics since the anisotropic Dirac cones lead to different values of Fermi velocities yielding variable carrier concentrations. In this work, the feasibility of the B-based hybrid monolayers BX (X = As, Sb, and Bi), as anisotropic Dirac cone materials is investigated. Calculations based on density functional theory and molecular dynamics method find the stability of these monolayers exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Recently, different polymorphs of boron and group V elemental (pnictogens) binary materials, i.e., BX (X = P, As, Sb, Bi), have been widely explored, using computational methods, for their potential applications. [22][23][24][25][26] Boron-and-pnictogen-based 2D sheets are usually stable in the hexagonal crystal group (h-BX) with structural features akin to those of graphene. Hexagonal boron phosphide (h-BP) shows promising applications in hydrogen storage with a gravimetric capacity of 4.92 and 4.56% for the one-sided adsorption of H 2 and 7.40 and 6.45% for the double-sided adsorption of H 2 with Li and Na decoration, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, different polymorphs of boron and group V elemental (pnictogens) binary materials, i.e., BX (X = P, As, Sb, Bi), have been widely explored, using computational methods, for their potential applications. [22][23][24][25][26] Boron-and-pnictogen-based 2D sheets are usually stable in the hexagonal crystal group (h-BX) with structural features akin to those of graphene. Hexagonal boron phosphide (h-BP) shows promising applications in hydrogen storage with a gravimetric capacity of 4.92 and 4.56% for the one-sided adsorption of H 2 and 7.40 and 6.45% for the double-sided adsorption of H 2 with Li and Na decoration, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…31 By contrast, BX materials also exhibit different 2D polymorphs apart from h-BX. [22][23][24][25][26] Porous BN phases show outstanding permeability and selectivity for hydrogen purification. 32 Zhu et al have reported different forms (a 1 -BP, b 0 -BP, b 1 -BP and g-BP) for the allotropes of BP.…”
Section: Introductionmentioning
confidence: 99%